Metales pesados (ni, cd, cu, mn, pb) en minería abandonada y su impacto en la calidad de agua del río pilaló, año 2019. - Hayman Moreira, Carmen (2020)
The presence and concentration of heavy metals in the water of rivers, seas, springs, deep wells, oceans, etc., is an increasingly frequent scientific task throughout the world. The accumulation and concentrations of these metals in water can lead to severe problems for health and aquatic ecosystems. Furthermore, the objective of the project was to determine the presence of the heavy metals nickel (Ni), Cadmium (Cd), Copper (Cu), Manganese (Mn), Lead (Pb) and Cyanide (CN- no metal) and its impact on the water quality of the Pilaló river. A diagnosis of the current situation of the Pilaló river water was carried out based on surveys. The presence of heavy metals was chemically analyzed, and a proposal for the recovery of the Pilaló river water was generated. To statistically validate the laboratory results, a completely randomized design (DCA) was used. The results of the surveys showed that the level of contamination is variable due to the existence of a mine which is located near the riverbank. It has been inactive for eight decades, yet it has been unloading heavy metals in the rainy season. On the other hand, chemical analyses allowed to determine that of all the metals analyzed (Ni, Cd, Cu, Mn, Pb plus CN-), Mn presented the highest concentration level (0.0717mg.L-1) in water from the Pilaló river. Despite being the metal with the highest concentration in the investigation, it did not show any effect on water quality. Hence, the proposal for a plan to recover water from the Pilaló river proposes promoting phytoremediation projects with seedlings that have these characteristics. Statistical analysis showed that there are no differences between treatments, but between metals. It is concluded that although the surveys carried out on the inhabitants of the study area indicated high levels of contamination, the results found in the laboratory demonstrate a contrary effect. Therefore, this investigation showed low levels of contamination by heavy metals plus CN- in the water of the Pilaló river, being recommended in the future, in addition to carrying out these chemical analyzes, biological and physical tests to determine the quality of the water in the Pilaló river, following national and international standards. Keywords: Contamination, levels, concentrations, heavy metals, river.